Enhancing Microstructural Characteristics and Mechanical Properties of Ti-Al-Dy Alloy through Ball Milling and SPS Consolidation - Hyunseung Lee; Si Young Chang (Archives of Metallurgy and Materials)
In this study, pure Ti, Al, Dy powders were ball-milled with zirconia balls in argon atmosphere for 3 h at 800 rpm, producing a Ti- 6 wt.% Al- 4 wt.% Dy alloy powder. The alloy powder was consolidated by SPS technique at 1373 K for 15 min under 50 MPa pressure in vacuum. The sintered body had approximately 99% in density and 6 μm in grain size. XRD and TEM revealed the presence of the second phases such as Ti3Al, Al3Dy and Ti4Al20Dy phases, and their sizes were approximately 50 nm. Microhardness was approximately 960 Hv at room temperature, which decreased as temperature increased. However, there remained the micro-hardness significantly higher compared to the commercial Ti-6Al-4V alloy. After hardness test at 1173 K, XRD analysis did not show any difference in peaks, while the grain size and second phases size increased by ~4 μm and ~2 nm, respectively.